Unlocking Biochar’s Potential: Innovative Strategies for Sustainable Remediation of Heavy Metal Stress in Tobacco Plants - Abdul Ghaffar Shar; Leyi Zhang; Anzhi Lu; Munib Ahmad; Muhammad Saqib; Sadam Hussain; Usman Zulfiqar; Pingping Wang; Lixin Zhang; Mehdi Rahimi (Scientifica)
Tobacco, being a globally cultivated crop, holds significant social and economic importance. Tobacco plants are susceptible to the adverse effects of heavy metals (HMs), particularly cadmium (Cd), which hinders root development, disrupts water balance, and impedes nutrient absorption. Higher concentrations of HMs, especially Cd, naturally accumulate in tobacco leaves due to complex interactions within the plant–soil continuum. The uptake of Cd by plants from the soil is influenced by several factors, including soil type, pH, irrigation water quality, and the chemical composition of the metal involved. Different techniques, such as bioremediation, phytoremediation, and mycoremediation, have been employed to tackle the issue of HMs. The use of biochar offers a practical solution to mitigate this problem. With its large surface area and porous nature, biochar can effectively alleviate HMs contamination. Under biochar application, metal adsorption primarily occurs through physical adsorption, where metal ions are trapped within the pores of the biochar. Additionally, electrostatic attraction, in which negatively charged biochar surfaces attract positively charged metal ions, is another major mechanism of metal remediation facilitated by biochar. In this review, we documented, compiled, and interpreted novel and recent information on HMs stress on tobacco plants and explored biochar’s role in alleviating HMs toxicity. By providing a comprehensive review of the persistent threat posed by Cd to tobacco crops and exploring biochar’s potential as a remediation measure, this work aims to enhance our understanding of HMs stress in tobacco and contribute to the development of sustainable agricultural practices.